PERLINDUNGAN HUKUM BAGI NASABAH BANK ATAS TERJADINYA CARD SKIMMING ATM - Syahputra, M.Ikhsan; Bachtiar, Maryati; Dasrol, Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
The existence of an electronic transaction systems are very supportive for economic movements, specially in financial transactions, with the result that encouraging public confidence in economy which actually prioritizes speed and efficiency which provides simplicity and convenience. Electronic transaction facilities that are widely used by the public are ATM. In addition to providing various conveniences for customers, ATMs can actually cause some problems for its users, such as ATM fraud using the skimming method which is detrimental to the user's customers that make customers unsecured. In Law Number. 8/1999 that describe about Consumers Protection, the rights of consumers are regulated, which is to get safety and comfort in using goods or services. Therefore, This thesis is to find out how legal protection for customers on consumers who experience ATM losses in the use or caused by third parties.This thesis method is using normative juridical research’s method. This research’s type is descriptive analytical. Sources of legal materials that used in this thesis are primary and secondary legal materials. This thesis’s data collection techniques using qualitative methods. Based on the results and discussion, it is concluded that there is no law or act that specifically regulates the use of ATMs and legal protection for customers, and legal protection for Indonesian customers is carried out by means of prudential principles and the bank must know every customers as institutions of public trust. In carrying out all its business activities, in this case including ATM services, banks can provide clear and transparent security; based on Paragraph 29 section 3 and section 4 of Law Number.10 of 1998 that concerning about Banking; then based on the regulation of the Financial Services Authority Number 1 / POJK.07 /2013 that concerning about Consumer Protection in The Financial Services Sector which is paragraph 25 that mentioned about the obligations of financial service business; legal protection for customer data by providing a system security that can protect customers and anticipate losses for customers when using ATMs, can be overcome by using an ATM card based on chip technology.Keywords: Legal Protection, ATM, Card skimming